Small-RNA sequencing reveals potential serum biomarkers for gallbladder cancer: results from a three-stage collaborative study of large European prospective cohorts - Blandino, Alice; Scherer, Dominique; Boekstegers, Felix; Rounge, Trine B.; Langseth, Hilde; Rössler, Stephanie; Hveem, Kristian; Brenner, Hermann; Pechlivanis, Sonali; Waldenberger, Melanie; Lorenzo Bermejo, Justo (European journal of cancer, 2025)
Gallbladder cancer (GBC) is an aggressive disease with limited treatment options but high prevention potential. GBC tumours take 10-20 years to develop, a timeframe that holds potential for early detection. MicroRNAs (miRNAs) play a central role in abnormal cell processes, and circulating miRNAs may constitute valuable biomarkers of early disease. We used microarray data to pre-select differentially expressed miRNAs in formalin-fixed paraffin-embedded (FFPE) gallbladder tissue samples (GBC n = 40, normal n = 8). We then applied small-RNA sequencing to screen for miRNA expression differences in serum samples from three European prospective cohorts (n = 37 GBC case-control pairs), and validated the most promising candidates in three independent cohorts (n = 36 GBC case- control pairs). Statistical analyses included robust linear regression, pathway and meta-analysis, and examination of expression correlation between miRNAs and target genes. MiR-4533 and miR-671-5p were overexpressed in GBC tissue and serum samples, and meta-analysis confirmed the overexpression of miR-4533 in GBC serum samples from the prospective cohorts (p-value = 4.1×10-4), especially in individuals of female sex, under 63.5 years, or with a BMI below 26.2 kg/m2. Pathway and correlation analyses revealed that miR-4533 targets SIPA1L2 in the Rap1 signalling pathway, and SIPA1L2 was downregulated in GBC serum samples. Our study highlights the advantage of integrating small-RNA sequencing results from different types of samples and independent datasets, and the need for international research collaborations to identify and validate biomarkers for secondary prevention of rare tumours such as GBC. The function of miR-4533 and its interaction with SIPA1L2 in GBC development need to be further investigated.
Gesehen am 25.07.2025